PENGEMBANGAN KOMPETENSI PEGAWAI PROVINSI JAWA TENGAH MELALUI IMPLEMENTASI JATENG CORPORATE UNIVERSITY - Agus Suharsono (JURNAL LITBANG PROVINSI JAWA TENGAH, 2022)
Article 203 of Government Regulation 17 of 2020 concerning Amendments to Government Regulation Number 11 of 2017 concerning the Management of civil servant/Pegawai Negeri Sipil (PNS) stipulates that employee competency development is carried out through an integrated learning system approach or Corporate University. Provincial Government of Central Java already has Central Java Corpu, but the number of employees who have attended training is only 3%, because the training is carried out classically at BPSDM, even though every employee has the right to take part in competency development for a minimum of twenty hours of training, so it is necessary to develop an appropriate design with the benchmark of the Ministry of Finance Corpu. This study used a descriptive approach by means of library research and analyzed logically-inductively. The results of the study indicate that it is advisable to make a Governor's Regulation concerning Central Java Corpu which regulates that its characteristics are: relevant, applicable, impactful, and accessible; using the 70-20-10 model of learning; developed using the ADDIE model; and built knowledge management.